Knowledge and practice of foot self-care among Jordanians with diabetes: An interview-based survey study - Abu-Qamar, Ma'en (Mark Allen Publishing Ltd., 2014)
Objective: To examine knowledge and practice of foot care among Jordanian patients with diabetes.Method: An ethically-approved Arabic language questionnaire was used to interview participants version 16). Total scores for knowledge and practice were computed, and were classified as poor (<50%), satisfactory (50–70%) or good (>70%). Results: Out of 1085 participants, 51.1% were males and 48.8% were females. The average age was 53.3 years (SD = 13.3 years), with over half (54.0%) were between 41–60 years of age. More than half of knowledge scores were within the range “good”, in which there was around 6% of the practice scores. Those classified as having poor knowledge amounted to 7.2%, whilst those classified as exercising poor practice amounted to 42%. Statistically significant associations were established between level of education and knowledge (p<0.001) as well as practice (p<0.006). Conclusion: The study demonstrated discrepancies between knowledge and practice in relation to foot care. Efforts are required to reduce these discrepancies between knowledge and the real practice of foot self-care, taking into account the patients' levels of education and the cultural context.